Endgame Rudolf Nureyev remembered by the Royal Ballet, reviewed - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Rudolf Nureyev tribute. In Raymonda Guillem holds her perfermance a hairsbreadth this side of caricature. PALABRAS CLAVE: Rudolf Nureyev, Royal Ballet, tribute, Pushkin's Eugene Onegin, Apollo, Raymonda, Images of Love.